The Use of Problem Solving Methods to Improve Indonesian Language Learning Outcomes in Fourth Grade Students of SDN Segeran IV Indramayu Academic Year 2025/2026 - Farihiyah Farihiyah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Learning outcomes are the abilities students acquire after learning activities.Evidence that someone has learned is a change in behavior in that person, for example from not knowing to knowing and from not understanding to understanding. The learning process in class IV SDN Segeran IV is still less active, so that students are less enthusiastic about learning, many students are busy chatting with their friends and some even play around so that it causes a lack of focus on learning and the material is not conveyed completely to all students, this condition causes low student grades in Indonesian subjects. Based on these problems, researchers made an effort to improve the learning process through the application of the Problem Solving method. The formulation of the problem in this study is whether the use of the problem solving method can improve the learning outcomes of Indonesian subjects for class IV students of SDN Segeran IV. The purpose of this study is to determine the improvement in learning outcomes by using the Problem Solving method. The purpose of this study is to improve the Indonesian language learning process for class IV students of SDN Segeran IV in the 2026/2027 Academic Year. The study uses the PTK model with the application of the problem solving method in improving the learning outcomes of Indonesian subjects for class IV students of SDN Segeran IV Indramayu in the 2025/2026 Academic Year. Data collection was carried out by observing student activities and test sheets to determine the improvement in student learning outcomes. From the results of the analysis that has been done, it is known that the problem solving learning method can improve student learning outcomes in the Indonesian language subject at SDN Segeran IV. This can be seen from the percentage of post-test results, there was an increase of 25% from cycle I with results of 70% and cycle II 95%. So it can be concluded that using the Problem Solving method can improve learning outcomes in the Indonesian language learning process for fourth-grade students at SDN Segeran IV Indramayu in the 2025/2026 Academic Year.